2014
DOI: 10.1186/1742-4755-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Toll free mobile communication: overcoming barriers in maternal and neonatal emergencies in Rural Bangladesh

Abstract: BackgroundToll free mobile telephone intervention to support mothers in pregnancy and delivery period was tested in one sub district of Bangladesh. Qualitative research was conducted to measure the changes of mobile phone use in increasing communication for maternal and neonatal complications.MethodsIn-depth interviews were conducted among twelve Community Skilled Birth Attendants and fourteen mothers along with their husbands prior to intervention. At intervention end, six Community Skilled Birth Attendants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 18 publications
1
61
0
Order By: Relevance
“…Seven articles studied communication between a health worker and patients, with the emphasis on improving health worker efficiency by saving travel time and gaining work time 11,12,22,2528 . Texts focused on increasing access to skilled attendants at birth 26 , patient medication adherence 22,25 , appointment reminders 22,26 , and tracking patients 11,12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven articles studied communication between a health worker and patients, with the emphasis on improving health worker efficiency by saving travel time and gaining work time 11,12,22,2528 . Texts focused on increasing access to skilled attendants at birth 26 , patient medication adherence 22,25 , appointment reminders 22,26 , and tracking patients 11,12 .…”
Section: Resultsmentioning
confidence: 99%
“…Twelve articles studied communication between health workers 12,2224,2835 . Communication by mobile phone was highly acceptable to health workers 3032 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all of the study show that mobile health application help mother and father to enhance health status on her pregnancy especially for working mom (Chaves et al, 2017;Premji, 2014;Jennings et al, 2016;Obasola, Mabawonku, & Lagunju, 2015;Felicie et al, 2016;Ledford et al, 2016;Mcnabb et al, 2015, Waring et al, 2014Spiby et al, 2014, Asiodu et al, 2015Rhyne & Borawski, 2014;Guerra-reyes et al, 2017;Smith) . Inline with previous study from Western countries, the 7 studies from non-Western countries including Africa, India, Bangladesh, Australia found that mobile health can give positive impact for pregnant mom Balakrishnan et al, 2016;Forti, Stapleton, & Kildea, 2013;Huq, Azmi, Quaiyum, & Hossain, 2014;Khatun et al, 2015;Lupton & Pedersen, 2016;Khatun et al, 2017). In Indonesia, several studies have been conducted about this topic and its show that utilizitation of mobile health as health promotion media still in progress (Santoso, 2017;Probandari, Arcita, Kothijah, & Pamungkasari, 2017 …”
Section: Methodsmentioning
confidence: 97%
“…The use of mobile health as one of the effective solutions recommended by the WHO in the healthcare process continues to grow (Balakrishnan et al, 2016;Forti, Stapleton, & Kildea, 2013;Huq, Azmi, Quaiyum, & Hossain, 2014;Santoso et al 2017). The process of health care includes the exchange of information, communication and consultation using smart phones owned by the majority of the population in various countries (Ayiasi et al, 2016;Khatun et al, 2015;Vital Wave Consulting, 2010).…”
Section: Discussionmentioning
confidence: 99%